Classification in the organisation of Digital Documentary Systems: criticalities and new perspectives - Maria Guercio (JLIS.it, 2017)
The article presents a reflection on the Archival Classification with specific reference to the role that this function plays in Digital Documentary Systems. Those aspects have been dealt with in depth both on the methodological and theoretical level and directly on the ground since mid-Nineties of the last century; however, many relevant issues are still unanswered, despite the development of specific software and standards. This paper analyses the recent Italian and International literature, and highlights the delays of the current disciplinary research and of the practical experiences of the last years, that in many cases show an impasse or even a recession phase.